To the problem of three-body-points with variable masses - Minglibayev, M Zh; Mayemerova, G M (Journal of Mathematics, Mechanics and Computer Science, 2011)
In given article are considered secular perturbations in the three-body problem with masses, changing isotropically by different specificrates. The analytical expressions of secular perturbations in the three-body problem with variable masses are obtained with the computer algebra system Mathematica.